Emerging RNA Viruses: Epidemiology, Pathogenesis, and Challenges for Vaccine Development: Review - Zahraa Hussein Obaid; Ahmed Saleem Abbas; Lubna Abd AlmuttalibAl- Shalah; Ghazi Mohamad Ramadan (Journal of Biomedicine and Biochemistry, 2026)
"For decades, emerging RNAviruses have continued to multiply and diversify constantly for humanity. Many regulations have been issued regarding different strains of coronavirus to combat human infection, and they do not cause the deaths of millions of people around the world.". Emerging RNA viruses, including coronaviruses, flaviviruses, and filoviruses, have demonstrated the ability to cause pandemics and outbreaks with devastating health and economic impacts. Their high mutation rates and zoonotic potential complicate public health responses. This review provides a detailed overview of the epidemiological trends of major emerging RNA viruses, their mechanisms of host infection and immune evasion, and the current challenges in vaccine development. Key obstacles include antigenic variability, cross-species transmission, and limited duration of immune protection. Advances in mRNA vaccine technology, vector-based vaccines, and universal vaccine strategies are also discussed. Proactive surveillance, rapid vaccine platforms, and global collaboration are emphasized as critical components for future preparedness.